The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0004-27492012000600016
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial keratoplasty: evolution and horizons

Abstract: Endothelial keratoplasty has been adopted by corneal surgeons worldwide as an alternative to penetrating keratoplasty (PK) in the treatment of corneal endothelial disorders. Since the first surgeries in 1998, different surgical techniques have been used to replace the diseased endothelium. Compared with penetrating keratoplasty, all these techniques may provide faster and better visual rehabilitation with minimal change in refractive power of the transplanted cornea, minimal induced astigmatism, elimination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Although the rabbit corneal endothelium and the human corneal endothelium are significantly different with respect to cell proliferation, our study is clinically relevant. Endothelial transplantation surgeries, such as Descemet’s membrane endothelial keratoplasty (DMEK), Descemet’s stripping endothelial keratoplasty (DSEK), and Descemet’s stripping automated endothelial keratoplasty (DSAEK), are frequently performed in the treatment of corneal endothelial diseases 40 , and the DM was normally stripped away, with a damaged endothelium, in these surgeries 41 . Long-term follow-up showed a high incidence of posterior stromal and graft interface haze 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the rabbit corneal endothelium and the human corneal endothelium are significantly different with respect to cell proliferation, our study is clinically relevant. Endothelial transplantation surgeries, such as Descemet’s membrane endothelial keratoplasty (DMEK), Descemet’s stripping endothelial keratoplasty (DSEK), and Descemet’s stripping automated endothelial keratoplasty (DSAEK), are frequently performed in the treatment of corneal endothelial diseases 40 , and the DM was normally stripped away, with a damaged endothelium, in these surgeries 41 . Long-term follow-up showed a high incidence of posterior stromal and graft interface haze 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, endothelial keratoplasties (EKs) account for approximately 54% of the procedures performed annually [2], exploited by surgeons worldwide as an alternative to PKs for the treatment of endothelial corneal disorders [30]. An EK involves the selective removal and replacement of the corneal endothelium [31] when only the endothelium is damaged.…”
Section: Keratoplastymentioning
confidence: 99%
“…Compared to a PK, the major benefit is the possibility of maintaining the structural integrity of the eye, thereby reducing the risk of rejection. Other advantages include a more effective and faster visual rehabilitation, minimization of induced astigmatism, and the elimination of some complications due to the final sutures [30,32,33]. This is evidenced by the decreasing annual number of PK procedures over the years in the United States, from 42,063 in 2005 to 19,294 in 2014.…”
Section: Keratoplastymentioning
confidence: 99%
“…Posterior lamellar keratoplasty has emerged as an alternative to PK to treat corneal endothelial pathology [63,64]. Evolution of the posterior lamellar keratoplasty procedures began with Melles et al, who reported deep lamellar endothelial keratoplasty (DLEK) that includes sutureless transplantation of posterior lamellae of cornea from a scleral incision [65].…”
Section: Oct In Posterior Lamellar Keratoplastymentioning
confidence: 99%